Analisis Kualitas Air dan Status Mutu Air Sungai Batang Asam Akibat Limbah Cair Kelapa Sawit Menggunakan Metode Indeks Pencemaran - Siti Umi Kalsum; Lailal Gusri; Junardi Junardi (Universitas Batanghari Jambi, 2018)
Batang Asam River as a source of raw water for Drinking Water Supply Systems (SPAM) and daily needs. On May 19, 2015 there was pollution in the Batang Asam River due to the spillage of palm oil wastewater from one of the palm oil companies around the Batang Asam River. The water river becomes smelly and black and many fish die. The initial testing showed that BOD parameter = 10 mg / l), COD = 50 mg / l, TSS = 16 mg / l, N-Total = 3.86 mg / l, pH = 6.02, Oil and fat = 2.8 mg / l, where almost all parameters above the quality standard. The purpose of this study was to analyze status of water and water quality of Batang Asam River Using Pollution Index Method as a result of spilling palm oil wastewater. Water sampling of the Batang Asam River was carried out in 4 (four) locations, namely the upstream area of Lubuk Bernai Village, the Central area of Lubuk Lawas Village and Tanjung Bojo Village and the downstream of Kampung Baru Village (Pengabuan River Estuary). Parameters tested were pH, TSS, TDS, BOD, COD, DO, Fe, Oil and fat based on Government Regulation Number 82 of 2001 concerning Water Pollution Control and Water Quality Management For Class II. Analysis of water quality status using the Pollution Index method based on the Minister of Environment Regulation Number 115 of 2003 concerning Guidelines for Determining the Status of Water Quality. The results showed that the analysis of the average waterquality of Batang Asam River from four locations tested were parameters pH 6,8, TDS parameters 79,5 mg / l, TSS parameters 15,25 mg / l, DO parameters 3,025 mg / l, BOD parameters 2,935 mg/l, COD parameters 14,5 mg / l, Fe 0,645 mg / l and parameters of oil and fat 1 mg /l satisfy the class II water quality standard (PP No. 82 of 2001). The status of Batang Asam River shows that the status of water quality is mildly polluted with a pollution index value of 1,0 ≤ IP ≤ 5,0 which is 1,96.